A new genus and species of micro bee fly from the Earliest Eocene French amber (Diptera: Mythicomyiidae: Psiloderoidinae) - Myskowiak, Justine; Garrouste, Romain; Nel, Andre (Zootaxa, 2016)
Mythicomyiidae, or micro bee flies, are tiny flies (0.5–5.0 mm) that are found throughout most parts of the world except the highest altitudes and latitudes (Greathead & Evenhuis 2001). Including all extinct and extant taxa, the Mythicomyiidae currently comprise more than 380 valid taxonomic species distributed among 30 genera. The subfamily Psiloderoidinae is especially well represented among the fossil Mythicomyiidae by seven Cretaceous or Cenozoic genera. We here describe a new genus and a new species of this subfamily based on fossils from the Earliest Eocene of Oise (France). A Psiloderoidinae, Proplatypygus matilei Nel & DePloëg, 2004, is already described in this amber. Another mythicomyiid, Eurodoliopteryx inexpectatus Nel, 2006, is the most frequent bombylioid in this amber (Nel & DePloëg, 2004; Nel, 2006).